Design and Development of A Three-Point Auto Hitch Dynamometer for An Agricultural Tractor - A. F. Kheiralla; A. Yahya; M. Zohadie; W. Ishak (ASEAN Journal on Science and Technology for Development, 2003)
This paper describes the design, development and calibration of a three-point auto hitch dynamometer for measuring the horizontal and vertical forces that existed at the three-point hitch of an agricultural tractor.  The design concept of the dynamometer was based on an instrumented inverted U frame assembly that was mounted between tractor links and implement. The design incorporates for both lower point hitch spread and mast height adjustments, and quick hitch capability in accordance with category 1 and II three-point hitch system.  The force sensing elements were comprised of three steel extended octagonal ring transducers that were located between the inverted U frame and hook brackets.  Electrical resistance strain gauges were mounted on the extended octagonal ring transducer at strain angle nodes to independently monitor strains that were proportional to the horizontal and vertical forces at the ring center. Each transducer was designed for maximum horizontal and vertical forces of 25 kN and 10 kN at measurement mean sensitivities of 25.19 µStrain/kN and 25.60 µStrain/kN, respectively. However, the complete dynamometer has been designed to measure the maximum resultant horizontal and vertical forces of 50 kN and 20 kN, respectively.  Field demonstration tests on the dynamometer and data acquisition system showed that they were able to function effectively as intended.  The data acquisition system was able to successfully scan and record the dynamometer signals as programmed.  This dynamometer was part of the complete instrumentation system to be developed onboard a Massey Ferguson 3060 tractor for the generation of a comprehensive database on the power and energy requirements of the tractor and its working implement in the field.